化粧品原料の皮膚一次刺激性試験法の比較研究 モルモットクローズドパッチテスト - YOSHIKAWA Hirofumi; TSUYOSHI Takashi; OKAMOTO Kikuhiko; NAKAMURA Kazuhiro; Ito Katsutoshi; Imai Hiroshi (Skin research, 1984)
We performed several test methods for safety evaluation of cosmetic ingredients and products. Now we chose guinea pig closed patch test method. This study were performed in the 3 different laboratories. The test mamterials were propylene glycol, 1, 3-butylene glycol, glycerin, liquid paraffin, squalane, and pristane. We chose 100% propylene glycol and pristane as positive control, and distilled water as negative control. We performed this test with the same procedure in each laboratory. The results of this study were as following:(1) In three polyols, only 100% propylene glycol reacted but 1, 3-butylene glycol and glycerin showed no reactions.(2) In three hydrocarbons, the order of positive rate was pristane<liquid paraffin<squalane. Squalane showed almost all negative reactions.(3) The reactions of polyols diminished in the course of time. But the reactions of hydrocarbons continued for a time. 皮膚刺激性試験法の比較研究の一環としていくつかの多価アルコール, 炭化水素を用いて, モルモットによるクローズドパッチテストを実施した結果, 次の成績が得られた。1) 多価アルコールの反応の強さは, プロピレングリコール>1, 3-ブチレングリコール=グリセリンの順であった。反応は, 100%プロピレングリコールのみに認められ, 他はすべて反応を認めなかった。2) 炭化水素の反応の強さは, プリスタン>流動パラフィン#72> スクワランの順であった。このうち, スクワランは, ほとんど反応を認めなかった。3) 多価アルコールは, 経時的に反応が低下したが, 炭化水素は, 比較的持続的な反応を認めた。4) Draize基準による判定では, 紅斑の読み方に, 施設間差が認められた。